Arbuscular mycorrhiza differentially affects synthesis of essential oils in coriander and dill - Rydlová, Jana; Jelínková, Marcela; Dušek, Karel; Dušková, Elena; Vosátka, Miroslav; Püschel, David (Mycorrhiza, 2016)
Research on the role of arbuscular mycorrhizal fungi (AMF) in the synthesis of essential oils (EOs) by aromatic plants has seldom been conducted in field-relevant conditions, and then, only limited spectra of EO constituents have been analyzed. The effect was investigated of inoculation with AMF on the synthesis of a wide range of EO in two aromatic species, coriander (Coriandrum sativum) and dill (Anethum graveolens), in a garden experiment under outdoor conditions. Plants were grown in 4-l pots filled with soil, which was either γ-irradiated (eliminating native AMF) or left non-sterile (containing native AMF), and inoculated or not with an isolate of Rhizophagus irregularis. AMF inoculation significantly stimulated EO synthesis in both plant species. EO synthesis (total EO and several individual constituents) was increased in dill in all mycorrhizal treatments (containing native and/or inoculated AMF) compared to non-mycorrhizal plants. In contrast, EO concentrations in coriander (total EO and most constituents) were increased only in the treatment combining both inoculated and native AMF. A clear positive effect of AMF on EO synthesis was found for both aromatic plants, which was, however, specific for each plant species and modified by the pool of AMF present in the soil.
Keywords: Anethum graveolens; mykorhiza; oleje prchavé; Oils, Volatile; Mycorrhizae; kopr vonný; koriandr; Coriandrum